Newborn Pulse Oximetry Screening for Detecting Congenital Heart Disease: Experience at a Tertiary Care Center - Ziad R. Bulbul; Nour K. Younis; Farah Malaeb; Haytham Bou Hussein; Mariam Arabi; Fadi Bitar (Hindawi Limited, 2024)
Background. Congenital heart disease (CHD) remains the number one birth defect worldwide. Pulse oximetry screening (POS) is a widely used CHD screening modality effective in detecting critical lesions. This study is aimed at assessing the accuracy and cost-effectiveness of POS in a cohort of term well-babies admitted to a regular nursery in a tertiary care center. Methods. We reviewed the charts of term babies admitted to our regular nursery over a period of one year. The results of POS and the findings of echocardiography were collected. Similarly, we explored the records of our fetal echocardiography program to identify the fetuses screened for CHD during the same period. Results. 900 term babies were born and admitted to newborn nursery at our center, and 69 fetuses were evaluated by our fetal cardiology team during the study period. None of our term babies had a positive POS at birth or 24 hours of age. However, 56 babies had a cardiac echo before hospital discharge due to suspicious findings on physical examination or a family history of CHD. A simple noncritical CHD was noted in 10 of them. Additionally, 53 babies underwent echocardiography within the first five years of life; a simple CHD was noted in 6 of them. In parallel, 21 of our fetuses were found to have CHD: 16 simple CHD and 5 critical CHD (CCHD). Conclusion. Despite its cost-effectiveness and efficacy in screening for CCHD, POS is suboptimal for detecting simple CHD. In the absence of a proper prenatal screening and fetal echocardiography program, POS remains a cost-effective modality for detecting CCHD.